Parental experiences of caring for their preschool children after declining vaccines: a qualitative systematic review protocol. Issue 1 (24th January 2022) - Huel, Christine; Harding, Jillian; MacKinnon, Karen; Gordon, Carol; MacDonald, Shannon E.
ABSTRACT: Objective: This review will explore the experiences of parents after making the decision not to vaccinate their young children. This review aims to help health care providers understand parents' specific care strategies for their under-vaccinated or unvaccinated young children. Introduction: Much of the current qualitative research literature on parents who hesitate or refuse to vaccinate their young children focuses on parental perceptions about the safety and efficacy of vaccines and decision-making. However, limited attention has been paid to measures taken by parents to help their young children avoid contracting communicable diseases, promote resistance, and enhance their children's health. Inclusion criteria: This review will consider qualitative studies that describe parents' experiences of caring for their young children, aged 0 to six years, after making the decision not to vaccinate. Studies undertaken in any context will be considered. Studies that focus on young children who are unvaccinated or not fully vaccinated for reasons not related to parental refusal will be excluded. Methods: The JBI methodology for systematic reviews of qualitative evidence will be followed. Databases will be searched from 1998 onwards, and will include Web of Science, MEDLINE, CINAHL, PsycINFO, Google Scholar, and ProQuest Dissertations and Theses, with no language limits. Following critical appraisal, findings that describe parental experiences and the care activities they perform related to their young children will be extracted. The JBI process of meta-aggregation will be used to identify categories and synthesize findings. The ConQual approach will be used to assess confidence in the findings. Systematic review registration number: PROSPERO CRD42021241781